PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE PRACTICE REHEARSAL PAIRS TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWAKELAS VIII SMPN 1 LEMBAH MELINTANG KABUPATEN PASAMAN BARAT - Yumaliza, Novi; mukhni, mukhni; Yunita, Alfi (Pendidikan Matematika, 2014)
ABSTRACTÂ This research was designed for revealing whether the mathematics conceptual understanding of the students taught by using Practice Rehearsal Pairs was better than that of students taught by using conventional learning. This was an experimental research which used random toward the subject design. The population of the research was the students in class VIII of SMPN 1 Lembah Melintang. In collecting the data a quiz and a posttest were administered. The data gathered then was analyzed by using MINITAB. Based on the result of data analysis, it was found that the average score of the students in the experimental class (73,23) was higher than those in the control class (61,23). Thus, it was concluded that the mathematics conceptual understanding of the students taught by using Practice Rehearsal Pairs was better than that of students taught by using conventional learning in class VIII of SMPN 1 Lembah Melintang .